Pengembangan Sistem Informasi Budaya dan Wisata Kota Bima Berbasis Mobile-Web dengan Evaluasi Usability Menggunakan System Usability Scale (SUS) - Ian Moh. Rohmad Nuryanto; Tri Widodo Tri Widodo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
This study aims to develop a mobile-web-based Cultural and Tourism Information System for Bima City and evaluate its usability using the System Usability Scale (SUS) method. The system development process consisted of requirement identification, system design, implementation, and usability testing stages. The developed system provides several features, including cultural catalogs, interactive tourism maps, tourism destination information, and an administration panel accessible through mobile and desktop devices. Usability testing was conducted involving 25 respondents using a SUS questionnaire distributed through Google Forms. The results showed that the system was successfully implemented with a responsive and user-friendly interface. Based on the SUS calculation, the system achieved an average score of 81.24, which falls into the Excellent category. These results indicate that the system has a very good level of usability and is capable of providing effective, efficient, and satisfying user experiences. This research is expected to support digital tourism promotion and cultural preservation in Bima City through an integrated information system.